2019
DOI: 10.26740/jppipa.v3n2.p72-76
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Modul Tematik Berbasis Integrasi Islam Dan Sains Pada Tema Energi Dan Perubahannya Terhadap Hasil Belajar Siswa Mi Murni Sunan Drajat Lamongan

Abstract: Modul tematik berbasis integrasi Islam dan sains merupakan bahan ajar yang memuat seluruh kompetensi inti dalam pembelajaran tematik. Pada Modul ini Kompetensi Inti 1 yaitu spiritual termuat dalam bentuk integrasi al-Qur’an dengan materi pada tema energi dan perubahannya. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan Modul Tematik Berbasis Integrasi Islam dan Sains pada Tema Energi dan Perubahannya terhadap hasil belajar siswa MI Murni Sunan Drajat Lamongan. Penelitian ini merupakan penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The level of student understanding can be strengthened by teaching materials (Astiti, 2018). These results are corroborated by Faizah's (2019) thinking explaining that the thematic module with the integration of islam and science is very good and strengthens students' understanding in the learning process. The same thing is also explained by Prajawinanti (2020 that teaching materials can help students and teachers in the learning process.…”
Section: Introductionmentioning
confidence: 57%
“…The level of student understanding can be strengthened by teaching materials (Astiti, 2018). These results are corroborated by Faizah's (2019) thinking explaining that the thematic module with the integration of islam and science is very good and strengthens students' understanding in the learning process. The same thing is also explained by Prajawinanti (2020 that teaching materials can help students and teachers in the learning process.…”
Section: Introductionmentioning
confidence: 57%
“…Fokus kajian integrasi Islam dan Sains di Sekolah IT juga berhasil menyasar penelitian pengembangan sebagaimana yang dilakukan oleh Siska Arimadona yang berhasil menyusun modul biologi berbasis integrasi Islam dan Sains dengan tingkat validasi sebesar 79,11 % (Arimadona, 2016). Silvia Nur Faizah membuktikan bahwa modul tematik yang disusun dengan berbasis integrasi sains dan ilmu keislaman pada tema energi dan perubahannya terbukti meningkatkan hasil belajar sehingga diharapkan mampu mengakomodasi kebutuhan intelektual dan spiritual siswa ketika memasuki sekolah Madrasah Tsanawiyah (Faizah & Mubin, 2019 Petunjuk pedoman yang dijadikan alat analisis dalam penelitian ini adalah bagaimana lembaga pendidikan Islam menjadikan ilmu-ilmu keislaman yang berbasis wahyu sebagai landasan spiritual, moral dan akhlak manusia. Selanjutnya, lembaga pendidikan Islam dapat memosisikan bidang ilmu sains sebagai basis teknologi untuk memanfaatkan sumber daya alam tanpa eksploitasi liar.…”
Section: Pendahuluanunclassified
“…Analysis of various articles that have been published in various journals on science modules based on the integration of Islam and science has also been carried out by Faizah & Mubin (2018), Latifah (2016), and Anggraini (2018), the results of the study found that the use of modules ineffective learning improves student learning outcomes. Research on teaching materials containing scientific literacy was also conducted by Safitri et al (2015), and Rostikawati and Permanasari (2016), that found that teaching materials can increase students' scientific literacy Integrated science teaching materials developed by Firmansyah (2014) and Puspaningtyas (2015) can also increase student scientific literacy.…”
Section: Introductionmentioning
confidence: 99%